2015
DOI: 10.1002/adem.201500411
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Nitriding and DLC Coatings for Corrosion Protection of Precipitation Hardening Stainless Steel

Abstract: A duplex treatment, combining a nitriding diffusion process and the deposition of DLC coatings is investigated as an option for corrosion protection of precipitation hardening steels, in order to increase the service life of components used in plastic injection molds. Hardness and mechanical resistance are determined and the corrosion resistance in two different media is analyzed. Non-coated nitrided and non-nitrided samples are also tested for comparison. Corrosion resistance is investigated by means of immer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Figure 13 shows a schematic illustration for the corrosion behavior of multilayered film in NaCl solution. In general, DLC film may always have some defects such as pinholes or microcracks that allow the corrosive medium such as Cl − to diffuse in the film, where a localized galvanic corrosion can preferably occur and then expand and delaminate the film [42,43]. In case of multilayered DLC films, the improvement of corrosion resistance is attributed to the local coverage of defects like pinholes by an increasing number of Si-DLC layers and make the electrolyte encounter a more tortuous path in traversing the films.…”
Section: Discussion Of High Corrosion Resistancementioning
confidence: 99%
“…Figure 13 shows a schematic illustration for the corrosion behavior of multilayered film in NaCl solution. In general, DLC film may always have some defects such as pinholes or microcracks that allow the corrosive medium such as Cl − to diffuse in the film, where a localized galvanic corrosion can preferably occur and then expand and delaminate the film [42,43]. In case of multilayered DLC films, the improvement of corrosion resistance is attributed to the local coverage of defects like pinholes by an increasing number of Si-DLC layers and make the electrolyte encounter a more tortuous path in traversing the films.…”
Section: Discussion Of High Corrosion Resistancementioning
confidence: 99%
“…Corrosion behaviours of DLC coatings on nitrided steel substrates have been investigated in few studies [11, 18, 19]. Jellesen et al [18] have shown that corrosion resistance of low‐temperature plasma nitrided SS could be improved after applying a DLC thin film.…”
Section: Introductionmentioning
confidence: 99%
“…Azzi et al [11] investigated the improvement of the corrosion resistance of DLC thin films on plasma nitrided 316L SS with increasing breakdown potential ( E bd ) and decreasing corrosion current. In the most recent study, Dalibón et al [19] have reported that the corrosion resistance of plasma nitrided Corrax SS could be improved by DLC thin films with increasing E bd , but there was no significant effect on the reduction of corrosion current density.…”
Section: Introductionmentioning
confidence: 99%